Power Point Media Development for Increase Liveliness Study Students in Social Sciences Subjects at SD Negeri 1 Bahomotefe Regency Morowali - Munawir; Haliadi; Hasdin (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Demands education 21st century to be challenge separately for educators .​ Creative teacher can develop skills , ideas, and methods teaching new . Instructional Media is group instruments used by teachers for convey instructions or inside information lessons and as effort communicate with student about source Study . As presenter or something distributor message . Formulation problem How teachers develop Power Point media on the eyes social studies lessons in Class V of SD Negeri 1 Bahomotefe Regency Morowali , How? liveliness Study students ' eyes social studies lessons in class V of SD Negeri 1 Bahomotefe Regency Morowali , Is You can use Power Point media increase liveliness Study students ' eyes social studies lessons in Class V of SD Negeri 1 Bahomotefe Regency Morowali . Research purposes Analyze influence Power Point media development towards liveliness Study students ' eyes social studies lessons in Class V of SD Negeri 1 Bahomotefe Regency Morowali . Study This use type study development ( Research and Development). Research and development methods or in Language English Research and Development is method research used​ For produce product certain , and test effectiveness product the . Development results from study This is in the form of power point media containing material social studies learning , learning videos , and exercises created and designed use application canva .